(3Yed ef WH def MHs - (3CHh YHO Gddg dSGf GdOjf eMeO Hf YHO Gddg Hf SYjO GHf GdNWjH GdZQfGWi GdCfOdSj,J (B776 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj Ndb GdEfSGf ef fWaI CeTGL jfbSe gPG GdcJGH Edi LRFjf , CMOgeG JYOjO GdeQGV ef QCS Edi bOe , eGYOG eG jJYdb HGdRjfI s
(3BNQgG (B:s
(3hGeG eG hbY ef GdcdGe ai GdaQhL abO GYJPQ HCf Jdc GdMjd ef OhGYj EZJHGW GdCRhGL hHhGYK ehOGJgf hCSHGH feh GdfSd hGddg YRhLd jLYdfG eef YQa bOQg gh MSHfG hfYe Gdhcjd s
(3hgPg GdfSNI gj GdJi bOegG GdeDda Edi GdeSJYjf HGddg CHj SGe GdeQjfjs
(3ef edhc Hfj eQjT HGdeZQH GdCbUi hGdeJhaj SfI (B762s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B161 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs